Once a useful engine: a multilevel ethnographic case study on the transgenerational transmission of migratory trauma in Mexican-American families in a sanctuary city - Fernández-Apan, Maria Luisa; Hamui-Sutton, Liz (Frontiers in Psychiatry, 2025)
This article explores migratory trauma from an anthropological perspective, using the case study of Dani, a Mexican-American adolescent diagnosed with autism and anxiety. Through an extended case methodology and the use of ethnographic vignettes, it examines the transgenerational transmission of trauma in migratory contexts, along with the school, linguistic, and emotional barriers migrant families face. The interpretive analysis of Dani ‘s drawing, Once a Useful Engine, serves as a central narrative device, symbolizing the tension between agency and structure in the lived experience of trauma. The article offers a situated reading of suffering, grounded in the concepts of memory, structural violence, and the micro, meso, and macro-level dynamics shaping Dani ‘s and his family’s trajectory. Findings underscore the need for culturally responsive intervention models and propose public policy recommendations aimed at addressing the complexity of migrant family experiences in a more integrative and just manner.